'FIFA 11 for Health' for Europe. 1: effect on health knowledge and well-being of 10- to 12-year-old Danish school children. Issue 20 (29th April 2016) - Fuller, Colin W; Ørntoft, Christina; Larsen, Malte Nejst; Elbe, Anne-Marie; Ottesen, Laila; Junge, Astrid; Dvorak, Jiri; Krustrup, Peter
Abstract : Aim: To modify the 'FIFA 11 for Health' programme to the European situation, and to assess its effects on health knowledge and well-being in Danish school children. Method: A two-cohort study with seven intervention and two control schools. Of the 546 Danish children (boys 269; girls 277) of mean age 11.1 (±0.4) years from five city and four country-side schools, 402 undertook the 'FIFA 11 for Health' programme and 144 acted as controls. As part of each school's PE curriculum, seven intervention schools received a 45 min Play Football period (football skills and 3 vs 3 games) and a 45 min Play Fair period (health issues and football drills) on a weekly-basis for 11 weeks. Control participants continued with their regular school PE activities. Participants completed preintervention and postintervention health knowledge and well-being questionnaires. Results: Overall, health knowledge increase was significantly (p<0.05) greater for the intervention group (11.9%) than the control group (2.6%). Significant (p<0.05) between-group differences were obtained for 8 of 10 health topics (6.1–20.2%) related to physical activity, nutrition, hygiene and well-being. The social dimension of the well-being questionnaire was significantly (p<0.05) improved in the intervention group compared to the control group, but there were no significant between-group effects for the physical, emotional and school dimensions. Positive reporting about the programme was given by 72.4% of the children and only 4.8% reported negatively. Conclusions: The 'FIFA 11 for Health' programme modified for Europe demonstrated positive effects on children's health knowledge and social dimension of well-being, thereby providing evidence that the football-based health education programme can be used effectively within a European school's curriculum to increase physical activity, well-being and health knowledge.